THE SIGNIFICANCE OF THE USE OF COMPUTED TOMOGRAPHY IN PATIENTS WITH BRAIN TUMORS IN THE EARLY POSTOPERATIVE PERIOD - Sotvoldiev B. I.; Yakubov N. I. (Web of Journals Publishing, 2024)
The current state is characterized by the increasing use of CT, MRI, DSA and PET for the diagnosis of various types and types of brain tumors. The use, primarily of CT and MRI, significantly improved not only the recognition of brain tumors, but also made it possible to carry out differential diagnostics between them and non-neoplastic diseases of the brain. This article has published a broad review of the issues of computed tomography in patients with postoperative conditions with brain tumors. It has been shown that the CT method provides accurate and correct diagnosis, speed, and, most importantly, the preference of this method today.
Keywords: radiation diagnostics, tumor, central location, CT.